Impact of Preinjury Antithrombotic Therapy on 30–Day Mortality in Older Patients Hospitalized With Traumatic Brain Injury (TBI) - Rønning, Pål; Helseth, Eirik; Skaansar, Ola; Tverdal, Cathrine; Andelic, Nada; Bhatnagar, Rahul; Melberg, Mathias; Skaga, Nils Oddvar; Aarhus, Mads; Halvorsen, Sigrun; Helseth, Ragnhild (Frontiers in Neurology, 2021)
Objective: Elderly patients are frequently in need of antithrombotic therapy for reducing thrombotic events. The association between antithrombotic drugs and survival after traumatic brain injury (TBI) is, nevertheless, unclear. Methods: This retrospective study included patients ≥65 years admitted to a Norwegian Level 1 trauma center with TBI identified on cerebral computed tomography (cerebral-CT) during 2014–2019. Preinjury use of antiplatelets and anticoagulants was compared to the prescription rate in the general Norwegian population. The primary outcome was 30-day mortality. Uni- and multivariate logistic regression analyses estimated the association between the use of antithrombotic drugs and mortality. Results: The study includes 832 consecutive TBI patients ≥65 years. The median age was 76 years, 58% were males, 51% had moderate or severe TBI, and 39% had multiple traumas. Preinjury use of antithrombotics was registered in 471/832 (55.6%) patients; antiplatelet therapy alone in 268, anticoagulant therapy alone in 172, and combined antiplatelet and anticoagulant therapy in 31. Antiplatelet use did not differ between the study cohort and the general Norwegian population ≥65 years (31 vs. 31%, p = 0.87). Anticoagulant therapy was used more commonly in the study cohort than in the general Norwegian population (24 vs. 19%, p = 0.04). Combined use of antiplatelet and anticoagulant therapy was significantly associated with 30-day mortality, while preinjury antiplatelet or anticoagulation treatment alone was not. No difference in 30-day mortality between patients using VKA, DOACs, or LMWH was encountered. Conclusions: In this cohort, neither antiplatelet nor anticoagulant therapy alone was associated with increased 30-day mortality. Anticoagulant use was more prevalent among TBI patients than the general population, suggesting that anticoagulation might contribute to the initiation of intracranial bleeding after blunt head trauma. Combined antiplatelet and anticoagulant therapy posed increased risk of 30-day mortality.